Lending in the banking system under the conditions of marital state - Yuliia Halushko; Nuraya Melikova (Фінансово-кредитні системи: перспективи розвитку., 2024)
The banking sector is one of the most important components of the financial sector. The development of the credit services market is one of the indicators of the economic development of any country. Thanks to credit operations provided by banks, legal entities and individuals can attract additional monetary resources for their needs. Due to the corona crisis, banks around the world suffered certain losses. In 2022, Ukraine faced new challenges due to a military invasion that caused an economic crisis. However, the banking system of Ukraine continues to operate efficiently despite the risks and crisis situation.